2013
DOI: 10.1111/ger.12079
|View full text |Cite
|
Sign up to set email alerts
|

Tooth loss, chewing efficiency and cognitive impairment in geriatric patients

Abstract: Chewing efficiency seems stronger associated with cognitive impairment than the number of teeth. Hence, in a more holistic approach for the geriatric assessment, the dental examination may be complemented by a chewing efficiency test.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
106
0
4

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(119 citation statements)
references
References 54 publications
9
106
0
4
Order By: Relevance
“…Several qualitative reviews already stated the importance of good oral health in older people with dementia [7583]. This review summarizes that the number of teeth present is comparable between older people with dementia and cognitively intact older people [14, 15, 25, 39, 43, 51, 52, 58]. The number of teeth present was the most commonly used measure for dental health, presumably because of its simplicity.…”
Section: Discussionmentioning
confidence: 98%
“…Several qualitative reviews already stated the importance of good oral health in older people with dementia [7583]. This review summarizes that the number of teeth present is comparable between older people with dementia and cognitively intact older people [14, 15, 25, 39, 43, 51, 52, 58]. The number of teeth present was the most commonly used measure for dental health, presumably because of its simplicity.…”
Section: Discussionmentioning
confidence: 98%
“…The association between systemic health conditions and oral health has been examined in many studies [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] . Individuals with systemic health condition such as obesity, diabetes, hypertension, and hypercholesterolemia were found to have higher risk of developing periodontal disease than those without systemic health conditions [5][6][7][8][9][10][11][12] .…”
Section: Introductionmentioning
confidence: 99%
“…Individuals with systemic health condition such as obesity, diabetes, hypertension, and hypercholesterolemia were found to have higher risk of developing periodontal disease than those without systemic health conditions [5][6][7][8][9][10][11][12] . In addition, obesity was associated with tooth loss among elderly aged 70 years and over 1 [13][14][15] . Longitudinal studies also revealed a causal relationship that people with obesity were more likely to develop periodontal disease 16,17) .…”
Section: Introductionmentioning
confidence: 99%
“…1 Loss of teeth, and its subsequent decrease in masticatory ability and efficiency, is one of the most frequent conditions affecting quality of life in numerous ways, 2,3 even resulting in cognitive impairment in older adults. 4 Given the above, some authors 5,6 point out that the restoration of an adequate masticatory function is one of the main goals in dentistry as it improves dietary, systemic, mental and physical functions of the human body. The use of removable prostheses is still a viable and widely used treatment.…”
Section: Introductionmentioning
confidence: 99%